Use of the new preservation solution Custodiol‐MP for ex vivo reconditioning of kidney grafts. Issue 9 (4th May 2021) - von Horn, Charlotte; Wilde, Benjamin; Rauen, Ursula; Paul, Andreas; Minor, Thomas
Abstract: Organ shortage and the increasing use of extended criteria donor grafts for transplantation drives efforts for more efficient organ preservation strategies from simple cold storage toward dynamic organ reconditioning. The choice of a suitable preservation solution is of high relevance in different organ preservation or reconditioning situations. Custodiol‐MP is a new machine perfusion solution giving the opportunity to add colloids according to organ requirements. The present study aimed to compare new Custodiol‐MP with clinically established Belzer MPS solution. Porcine kidneys were ischemically predamaged and cold stored for 20 hours. Ex vivo machine reconditioning was performed either with Custodiol‐MP ( n = 6) or with Belzer MPS solution ( n = 6) for 90 minutes with controlled oxygenated rewarming up to 20°C. Kidney function was evaluated using an established ex vivo reperfusion model. In this experimental setting, differences between both types of perfusion solutions could not be observed. Machine perfusion with Custodiol‐MP resulted in higher creatinine clearance (7.4 ± 8.6 mL/min vs. 2.8 ± 2.5 mL/min) and less TNC perfusate levels (0.22 ± 0.25 ng/mL vs. 0.09 ± 0.08 ng/mL), although differences did not reach significance. For short‐term kidney perfusion Custodiol‐MP is safe and applicable. Particularly, the unique feature of flexible colloid supplementation makes the solution attractive in specific experimental and clinical settings.